Strategi Manajemen Pendidikan Perguruan Tinggi Agama Buddha Dengan Pendekatan Balanced Scorecard - Alexander Candra (Dhammavicaya : Jurnal Pengkajian Dhamma, 2020)
Research purposes: The digital age all changes must face, and sustainable human resource development. Need a study of changes in specialized colleges of Buddhism. The research aims to see how the competition of Buddhist higher education institutions produces quality graduates and can become the best teachers.Research methodology: This research uses a qualitative research methodology. Structured planning design, closed questionnaire form then tested the open questionnaire form. With respondents selected according to quality, then make an observation analysis, and theory.Results and Implications; The results of this study propose to maintain healthy quality competition, so expect all religious universities to join. With the combination of maintaining cost efficiency and competition